Apis mellifera colony productivity and growth influenced by initial frame strength: Farmer's perspective - SAINI, SUMIT; CHAUDHARY, O P; ANOOSHA, VADDE (The Indian Journal of Agricultural Sciences, 2018)
Beekeeping is a very good source of extra income to farmer and a very productive enterprise for landless farmers. Under Haryana condition there is unanimity among farmers and beekeepers regarding no. of frames to be kept while the season of honey production is about to start. Keeping this problem of farmers' in view present study was designed and implemented during 2014-15 and 2015-16 under semi-arid conditions of Haryana. Thirty six colonies with initially three (5, 10 and 15 frames) frame strength, twelve colonies in each were equalized (in terms of brood and food reserves) and transferred to experimental site. Strong colonies (15 frames) were observed superior in honey production (885.9 inches2), brood rearing (488.6 inches2 ) and pollen ( 129.2 inches2 ) reserves followed by medium strengths colonies having honey area 544.0 inches2 and lowest brood rearing and honey reserves ( 257.1 and 247.1 inches2 respectively) was observed in weakest colonies. Surviving with low strength weak colonies was observed with high egg area proportionate with strong and medium colonies. Observations were recorded throughout the major honey flow season for all growth parameters, average sealed honey area was recorded maximum in February (520.4 inches2) and a dip was observed in March (41.2 inches2 ) that is due to honey extraction and also due to end of honey flow season. Up and downs were observed in case of average total brood area but it keeps on decreasing after April and minimum on 31 May observation (286.8 inches2 ). Strong colonies with 15 frames was recorded with high brood area as compared to 5 and 10 frame colonies throughout the season which clearly indicates superiority of keeping good strength colonies at the start of honey flow season.